Occupational census profiling tool for librarians in the Philippines - Taban, Katrina O.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Addressing the lack of an official occupational census profiling tool for licensed librarians in the Philippines, this study identified the minimum set of questions needed for a comprehensive occupational census questionnaire which had been honed after taking into consideration response-specific and questionnaire design factors. Three cycles of questionnaire testing had been rolled out to a 42 participants through purposive sampling.

Two participants were filtered out by the questionnaires built-in filtering questions rendering 40 valid responses comprised entirely of licensed librarians in the Philippines. Respondents are not necessarily working in a library setting and can come from different institutions as long as they are licensed. Errors, issues encountered, and significant observations coming from valid responses have been tabulated, and analyzed.

Towards the end of this study, a questionnaire-based profiling tool specifically designed to gather occupational census data for librarians within the Philippines was created. The profiling tool was then recommended for further development by interested professional organizations, particularly in the field of Library and Information Science.
Thesis (Bachelor of Library and Information Science)
Keywords: Occupational census